Assessment of knowledge, attitude and practice towards disposal of unused and expired pharmaceuticals among community in Harar city, Eastern Ethiopia - Yohanes Ayele; Mulu Mamu (Taylor & Francis Group, 2018)
Background Pharmaceuticals are produced and consumed in increasing volume every year. Unfortunately, not all medications that go in to the hand of the consumers get consumed; large quantities remain unused or expire. The accumulation of medication at household and unsafe disposal of unwanted medicines could lead to inappropriate medicine sharing, accidental childhood poisonings and diversion of medicines to illicit use. Methods A descriptive cross-sectional study was conducted among 695 residents in kebele(ward) 16 of Jinela woreda(district), Harar city from February 27-April 27. A multi-stage sampling technique was used to select individual households. Face-to-face interview using structured questionnaires were conducted to collect data from each study subject. The cleaned data was entered in to epidata analyzed using SPSS version 20 software. Descriptive statistics on sample characteristics was computed including frequencies and percentage and presented using tables and figures. Results Most participants displayed correct understanding toward medication waste (72.9%) and its effect on environmental if disposed improperly (86%). A large portion of the respondents did not know about drug-take-back system 464 (66.9%). In order to minimize the entry of pharmaceuticals into environment, 68.6% of the participants suggested the need for proper guidance to the consumer. Majority of the respondents believed risk related to the presence of unwanted drug in home, potential harm to children, lack of adequate information on safe disposal practice and need for take-back program. Approximately 66% of the respondents had unused medicine stored at home and the common types of medicines kept in households were analgesics (62.7%) and antibiotics (24%). Preferred ways of disposal of both unused and expired medicine was throwing away in household garbage (53.2%) and two third of them disposed the pharmaceuticals in its original package and dosage form. Conclusion In present study, there was high practice of keeping medication at home and most disposal approach indicated by the participants was not recommended methods. Awareness about proper disposal of unused and expired medicines among the public should be created. Guidelines on safe disposal are required and an organized method of collecting unused and expired pharmaceuticals needs to be introduced.